MODEL KEBIJAKAN PEMERINTAH ACEH DALAM PELATIHAN TENAGA KERJA MIGRAN SELAMA COVID-19 - Muhibuddin; Nasrianti (Jurnal Transformasi Administrasi, 2021)
The main cause of the increase in unemployment in Aceh is due to the Covid-19 pandemic whose symptoms are global, so that it has an impact on the destruction of the National and Global economic order. The purpose of this study was to analyze the Aceh Government's Policy Model in Training Migrant Workers in COVID-19. The research approach is used by collecting primary data directly from the object of research through the stages of interviews with informants and respondents related to the object of research which is an empirical juridical research. Empirical juridical research, also known as empirical legal research, is a law that reviews from the point of view of external elements, namely an event that occurs in reality that affects legal behavior individually and in society as well as in legal institutions.The conclusions and suggestions from the results of this study are, the Policy of the Aceh Manpower and Population Mobility Service in Aceh Province in accepting prospective workers to be given education and training for migrant workers for internships in Japan is not socialized, and information on the acceptance of prospective workers through banners -banners placed on the National Crossroads of the Regency/City of Aceh Province. Based on Qanun Number 7 of 2014 concerning Employment, the Aceh Manpower and Population Mobility Service has the duty and responsibility to provide manpower training in Aceh Province even in the midst of the Covid-19 pandemic.